Aspects of Civil Rights and Their Integration into International Social and Environmental Legislation - KOSTRUBA, Anatoliy V. (Journal of Environmental Management and Tourism; Vol 9 No 5 (2018): JEMT Volume IX Issue 5(29) Fall 2018, 2018)
The paper examines the aspects of the formation of a legal situation in which civil rights and obligations can not only emerge but also modify and terminate on various grounds. The relevance of the study is determined by the fact that civil rights and responsibilities usually rely on basic normative acts, which formalize the structure of public relations. The problem calls for further investigation of the doctrinal aspects of the emergence, modification and termination of civil rights and obligations. Within regulation of social relations rights and responsibilities can also emerge in the absence of a relevant framework and get shaped in the course of the development of the legal system of the state. The purpose of the article is to offer classifications and to discuss the sustainable ways of regulation of civil rights and obligations for the state and participants of the legal process. The subject of the study is civil rights and duties within the legal environment for their implementation. Our interest is in the description of the conditions for improving the structure of the legal environment and the sustainable development of civil society in the future. The results of the research describe the directions and the forms of development of long-term legal regulation in the social state system and its integration into international social and environmental legislation.